A novel method combining stable isotopic labeling and high-resolution mass spectrometry to trace the quinone reaction products in wines. (30th July 2022) - Ji, Junfu; Liu, Xinyu; Hu, Xiaosong; Chen, Fang; Bueschl, Christoph; Schuhmacher, Rainer; Waterhouse, Andrew L.; Ma, Lingjun
Graphical abstract: Highlights: This study combines 13 C-labeling and high-resolution mass spectrometry. Quinone reaction products were detected by M and M + 6x peak feature-pairs. Sulfides largely quench quinones in white wines. Flavonoids react with quinones in red wine. Abstract: Quinone formation is a key initial step of wine oxidation. Nucleophiles sacrificially react with quinones to sustain color and aroma, but due to the complexity of wine, determining the identity of the constitutive nucleophile has been challenging. Here we apply a novel stable-isotope labelling approach combined with high-resolution mass spectrometry, using 13 C6 -labelled ortho -quinone. This allows for the specific detection of quinone reaction products with M and M + 6x peak feature-pairs in real wines. Analysis using MetExtract II successfully identified 225 quinone reaction suspects in negative mode in Sauvignon blanc wine, and 120 in Cabernet Sauvignon. Ten quinone reaction products with the most abundant peak areas were tentatively identified using a mass/structure workflow. It appears that sulfides largely quench quinones in white wines, whereas flavonoids are the dominant reactants in red wines. The latter result demonstrates how skin/seed extraction preserves red wine.